A Critical Review of Murabahah Practices in Indonesia Islamic Banks: A Sharia Perspective - Muliadi; Zainuri, Hamzah (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2025)
Murabahah is the most favored financing product among customers, contributing significantly to the growth of Islamic banking. With a straightforward scheme resembling typical sales transactions, murabahah focuses on fulfilling consumptive needs, similar to credit offered by conventional banks. As a result, banks do not need to worry about customers’ profits or losses, as the profit margin is predetermined from the outset. However, the adoption and adaptation of murabahah financing by Islamic banks have not been free from scrutiny and debate. Along with the development of the Islamic financial industry, questions have arisen about the extent to which murabahah truly reflects the spirit of authentic Islamic economic law. This research employs a qualitative methodology and is a library-based study emphasizing a scientific approach without involving statistical procedures. The study critiques various points of contention and debates surrounding murabahah products within the context of Islamic banking.